The Effect of Competency and Employee Engagement on Employee Performance in Public Sector Institutions - Mifta Haza Rahmayuna; Indra Sandakila (MASI Mandiri Edukasi, 2026)
This study examines the influence of competency and employee engagement on employee performance in public sector institutions in Indonesia. The research is motivated by persistent performance disparities within public sector organizations, which are frequently linked to misalignment between employee competency and job demands, as well as insufficient levels of employee engagement. The study aims to analyze the direct effects of competency and employee engagement on employee performance and to investigate the mediating role of employee engagement in the competency–performance relationship. A quantitative explanatory approach was employed, involving 105 employees from a public-sector institution selected via simple random sampling. Data were collected using a structured questionnaire with a five-point Likert scale measuring competency, employee engagement, and employee performance. Path analysis was used to test the hypothesized relationships among variables. The results reveal that competency has a positive and significant effect on employee performance, employee engagement has a positive and significant effect on employee performance, and employee engagement significantly mediates the relationship between competency and employee performance. These findings underscore the importance of integrating competency development and employee engagement strategies to enhance performance and organizational effectiveness in public sector institutions.